Non-phonological Strategies in Spelling Development - Salas, Naymé (Frontiers in Psychology, 2020)
This paper investigated the role that types of knowledge beyond phonology have on spelling development, such as knowledge of morpheme-to-grapheme mappings, of orthographic patterns, as well as word-specific orthographic patterns. It is based on the modern view that children do not learn spelling in discrete stages but, rather, they apply different types of strategies from early on. The goals of the paper were threefold: (1) to determine the relative difficulty of different types of non-phonological spelling strategies; (2) to examine the contribution of non-phonological strategies (specifically, morphological, morphophonological, orthographic, and lexical) to conventional spelling scores; and (3) to determine the role of children’s educational level and population type (first vs. second language learners) on spelling strategy use. A large sample of 982 children (497 boys), speakers of Catalan (a Romance language similar to Spanish but with a less consistent orthography) participated in the study. They were administered a bespoke dictation task aimed to test their conventional and phonographic accuracy skill, as well as to determine their ability to use different types of non-phonological strategies for the spelling of ambiguous phonemes. Data were analyzed with a series of multigroup, multilevel SEMs. Results showed that children across groups (1) found morphological and lexical strategies harder to apply than orthographic and morphophonological strategies; (2) all types of non-phonological strategies contributed greatly to spelling accuracy scores, even after controlling for children’s phonographic skills. Efficient strategy use increased as a function of schooling level, while second-language learners had a worse performance throughout, but no group showed a specific pattern of results. In conclusion, the paper offers substantial evidence that non-phonological strategies are paramount to learning to spell at least during the early and intermediate elementary school years. It is suggested that the teaching of writing should therefore be multidimensional in nature and target particularly the strategies with which children struggle the most: knowledge of morpho-graphemic mappings and word-specific lexical representations. Theoretical implications are also discussed.